The state of health of the Romany population in the Czech Republic - Nesvadbová, L; Rutsch, J; Kroupa, A; Sojka, S (Central European journal of public health, 2000)
The health state pilot study of Romany nationality people (432 adults and 105 children) intended on relationship between social characteristics and presentation of health problems, further on the index of absence from work due to illness and mutual relations. The frequent occurrence of diagnostic groups E10-14, F70-79 and M00-99 was found among the group of men. The results of investigation are valid in particular for our examined group.
Keywords: demografie; Medical Records; ukazatele zdravotního stavu; Demography; Health Surveys; Česká republika; chorobopisy; pilotní projekty; Child; Roma; dítě; Adult; dospělí; Romové; průzkumy a dotazníky; Czech Republic; lidé; Public Health; Humans; veřejné zdravotnictví; Family Health; zdravotnické přehledy; Pilot Projects; Health Status Indicators; Surveys and Questionnaires; zdraví rodiny